Sound insulation fireproof plate

By using flame retardant agel and inorganic modified filler formulas in the fireproof board, the problems of flammable and sound insulation performance of the wood-plastic composite board are solved, and the excellent flame retardant and sound insulation performance of the fireproof board is achieved to ensure that it is in Safety and applicability in various environments.

CN119192873AInactive Publication Date: 2024-12-27HANGZHOU YUNCHENG BUILDING DECORATION ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325614.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing wood-plastic composite panels are fire-resistant as fire-resistant boards that cause fire safety risks, and lack good sound insulation performance, which affects life and industrial production.

Method used

50 to 60 parts of bamboo powder, 40 to 50 parts of polypropylene resin, 0.5 to 0.9 parts of titanate coupling agent PN-130, 3 to 7 parts of flame retardant agel, 4 to 8 parts of inorganic modified filler, The formula of 1 to 3 parts of calcium and zinc stabilizer, 2 to 4 parts of dibutyl phthalate, 1 to 3 parts of stearic acid, 1 to 2 parts of antioxidant 1010 is modified by flame retardant agel and inorganic Preparation and application of fillers to improve the flame retardant and sound insulation performance of fireproof boards.

Benefits of technology

The prepared fireproof board has excellent flame retardant and sound insulation performance, which can effectively reduce fire safety hazards, ensure its applicability and safety under various environmental conditions, and broaden the use areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192873A_ABST
    Figure CN119192873A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fireproof plates, and discloses a sound-insulation fireproof plate which comprises the following raw materials: bamboo powder, polypropylene resin, a titanate coupling agent PN-130, flame-retardant aerogel, an inorganic modified filler, a calcium-zinc stabilizer, dibutyl phthalate, stearic acid and an antioxidant 1010. Wherein the flame-retardant aerogel is prepared by modifying a nitrogen-phosphorus flame retardant in the structure of Arabic gum; the inorganic modified filler is prepared by grafting polysulfide rubber to the surface of muscovite. The fireproof plate prepared by the invention can exert an excellent flame-retardant effect when a fire occurs, the destructiveness of the fire and the risk of casualties are reduced, the fireproof plate is endowed with excellent sound insulation performance, the applicability and safety of the fireproof plate under various environmental conditions are ensured, and the application field of the fireproof plate is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fireproof boards, and in particular to a sound insulation and fireproof board. Background Art

[0002] Boards are flat rectangular building material boards made of standard sizes. There are many types of boards, including solid wood boards, artificial boards, and special boards such as fireproof boards. Among them, fireproof boards, also known as fire-resistant boards, are a type of fire-resistant building material for surface decoration. They are widely used in interior decoration, furniture, kitchen cabinets, laboratory countertops, exterior walls and other fields.

[0003] Wood-plastic composite board is a kind of board made of plant fiber (such as wood powder, straw powder, bamboo powder, etc.) and thermoplastic polymer material (such as PE, PP, PVC, etc.) as the main raw materials, and adding appropriate additives, through mixing, hot pressing and other processes. It has the advantages of both wood and plastic and is widely used in furniture, construction, packaging and other fields. Wood-plastic composite board does not contain formaldehyde, which not only meets the requirements of green environmental protection, but also can be reused and recycled after being discarded. It is one of the important research directions in the current field of biomass material research. When wood-plastic composite board is used as fireproof board, due to the plant fiber and plastic (especially polyolefin plastic) They are all combustible or flammable materials. There are certain safety hazards if they are used directly indoors. When a fire occurs, the fire spreads rapidly, posing a great threat to the lives and property of consumers. In addition, in daily life and industrial production, noise pollution is increasing, seriously affecting people's physical health and quality of life. As an important part of a building, fireproof panels need to have good sound insulation properties to avoid noise interference, privacy leakage, affecting work efficiency and reducing the overall quality of the building. Therefore, wood-plastic composite panels need to have good fire resistance and sound insulation properties to ensure their applicability and safety under various environmental conditions.

[0004] In the prior art, the optimization of basic materials is one of the main means to improve the performance of wood-plastic composite boards. For example, the invention patent with publication number CN104497607B discloses a halogen-free flame-retardant wood-plastic composite material and its preparation method. The wood-plastic composite material is made of natural fibers, plastics, flame retardants, etc. as raw materials, and is prepared by mixing, extrusion plasticization, pelletizing, and injection molding processes. The flame retardant is a compound of polyphosphate, hypophosphite, and other flame retardants in a certain mass ratio. By introducing a composite flame retardant into the formula system and coordinating with other ingredients, the flame retardant properties of the wood-plastic composite material are effectively improved. Therefore, a wood-plastic composite board with excellent sound insulation and flame retardant properties can be obtained by introducing additives with sound insulation and flame retardant properties into the formula system. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a sound insulation and fireproof board.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A sound insulation and fireproof board comprises the following raw materials in parts by weight: 50-60 parts of bamboo powder, 40-50 parts of polypropylene resin, 0.5-0.9 parts of titanate coupling agent PN-130, 3-7 parts of flame retardant gas gel, 4-8 parts of inorganic modified filler, 1-3 parts of calcium zinc stabilizer, 2-4 parts of dibutyl phthalate, 1-3 parts of stearic acid, and 1-2 parts of antioxidant 1010.

[0008] Furthermore, the method for preparing the flame-retardant gas gel comprises the following steps:

[0009] S1: Add gum arabic to a mixed solution of N,N-dimethylformamide and deionized water, stir evenly with a magnetic stirrer, pass nitrogen protection, then add 1H-indazole-3-carboxylic acid and a catalyst to the system, after the addition, turn on the heating, wait until the system temperature reaches 95-105°C, stir at a constant temperature for 4-6 hours, stop heating and remove nitrogen, cool to room temperature and then discharge to obtain modified gum arabic;

[0010] S2: Add deionized water and toluene to the reactor, mix well, add modified gum arabic, stir well, pass nitrogen, expel air, then add tri(1-chloro-2-propyl) phosphate and alkaline catalyst, after the addition is completed, turn on the heating until the temperature in the reactor reaches 65-75°C, keep warm and stir for 6-10 hours, discharge the material, and freeze-dry to obtain a flame-retardant gas gel.

[0011] Furthermore, in step S1, the catalyst is any one of tetrabutyl titanate, tetraethyl titanate or tetraisopropyl titanate.

[0012] Furthermore, in step S2, the alkaline catalyst is any one of sodium carbonate, potassium carbonate or sodium bicarbonate.

[0013] Furthermore, in step S2, the freeze-drying process is: placing the material in a mold and letting it stand, after forming a gel, transferring the mold to a temperature condition of -15 to -25°C and storing it for 5 to 8 hours, and then transferring it to a freeze dryer and freeze-drying it at -48 to -52°C for 24 to 48 hours.

[0014] Furthermore, the preparation method of the inorganic modified filler comprises the following steps:

[0015] SS1: Add muscovite to toluene solution, ultrasonically disperse for 15-25 minutes, add acrylic acid and tetrabutyl titanate under continuous nitrogen conditions, mechanically stir evenly, raise the temperature to 95-105°C, keep warm for 3-6 hours, wait for the material to cool naturally, centrifuge to separate the solid material, wash the solid material, and vacuum dry to obtain modified muscovite;

[0016] SS2: Ultrasonic dispersion of modified muscovite in dimethyl sulfoxide solution to form a dispersion, polysulfide rubber and photoinitiator are added to the dispersion, the system is placed under ultraviolet light for 1 to 4 hours under stirring, the material is discharged, washed, and dried to obtain an inorganic modified filler.

[0017] Furthermore, in step SS2, the mass ratio of the modified muscovite to the polysulfide rubber is 1:0.4-0.9.

[0018] Furthermore, in step SS2, the photoinitiator is any one of benzoin ethyl ether, benzoin isopropyl ether or benzoin dimethyl ether.

[0019] Furthermore, the method for preparing the fireproof board comprises the following steps:

[0020] Step 1, adding bamboo powder, polypropylene resin and titanate coupling agent PN-130 into a high-speed mixer, premixing for 10 to 20 minutes, then adding inorganic modified filler, flame retardant gel, calcium zinc stabilizer, dibutyl phthalate, stearic acid and antioxidant 1010, and mixing at high speed for 20 to 30 minutes to obtain a mixture;

[0021] Step 2: placing the mixed material obtained in step 1 in a twin-screw extruder, setting the granulation temperature to 150-170° C., the screw speed to 100-200 r / min, and melt-extruding and granulating to obtain wood-plastic composite board pellets;

[0022] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 170-180°C and a pressure of 8-10 MPa for 15-20 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0023] Beneficial effects of the present invention:

[0024] (1) The present invention introduces flame retardant gas gel and inorganic modified filler into the preparation process of the fireproof board, so that the prepared fireproof board has excellent flame retardant and sound insulation properties, can play an excellent flame retardant effect in the event of a fire, reduce safety hazards, and give the fireproof board excellent sound insulation performance, so that it can effectively isolate external noise, ensure its applicability and safety under various environmental conditions, and broaden the application field of the fireproof board.

[0025] (2) The present invention prepares a flame retardant by modifying the structure of gum arabic with a nitrogen-phosphorus flame retardant. The gum arabic in the structure can be used as a carbon source, 1H-indazole-3-carboxylic acid can be used as a gas source, and tri(1-chloro-2-propyl) phosphate can be used as an acid source to form an intumescent flame retardant. When a fire occurs, a dense intumescent carbon layer can be formed to isolate the entry of heat and oxygen and restrict the continued combustion of the material. In addition, the gas formed during combustion has the advantages of being halogen-free, low-toxic, low-smoke and non-corrosive, which effectively improves the flame retardant performance of the fireproof board and reduces the destructiveness of the fire and the risk of casualties. In addition, the flame retardant gel is a porous material with high specific surface area, high porosity and low density. This porous structure can cause multiple reflections, refractions, scatterings and diffractions of sound waves when propagating in the material to achieve the consumption of sound energy, greatly blocking the conduction of sound waves, so that the prepared fireproof board has a sound insulation effect.

[0026] (3) The present invention obtains an inorganic modified filler by grafting polysulfide rubber onto the surface of muscovite. After the muscovite is organically modified, the interface performance between it and the matrix is ​​enhanced, and it can be relatively evenly dispersed in the matrix to form a good filling effect. On the one hand, muscovite can be used as a damping functional filler to improve the damping value of the material, and its layered structure causes sound waves to be reflected and refracted multiple times at the muscovite interface when propagating in the material, thereby increasing the propagation path of the sound waves, thereby consuming more sound energy and effectively improving the sound insulation performance of the fireproof board. In addition, the layered structure of muscovite can form a stable physical barrier layer in the matrix and produce a barrier effect, which can cooperate with the flame retardant gas gel to further improve the flame retardant performance of the fireproof board. On the other hand, since polysulfide rubber has good viscoelasticity, it can convert the energy of mechanical vibration and acoustic vibration into heat energy for dissipation, thereby achieving the purpose of noise reduction, blocking the propagation of sound, and further improving the sound insulation performance of the fireproof board.

[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0029] Figure 1 This is an infrared spectrum test chart of the modified gum arabic and the flame-retardant gas gel prepared in Example 1 of the present invention.

[0030] Figure 2 This is an infrared spectrum test chart of the inorganic modified filler prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] 1. Preparation of flame-retardant gel

[0034] S1: Add 5 g of gum arabic to a mixed solution of N,N-dimethylformamide and deionized water in a volume ratio of 1:1, stir evenly with a magnetic stirrer, pass nitrogen protection, then add 1.2 g of 1H-indazole-3-carboxylic acid and 0.05 g of tetrabutyl titanate to the system, and after the addition, turn on the heating, and after the system temperature reaches 100°C, stir at a constant temperature for 5 hours, stop heating and remove the nitrogen, cool to room temperature and then discharge to obtain modified gum arabic;

[0035] S2: Add 50 ml of deionized water and 50 ml of toluene into the reactor, mix well, add 5 g of modified gum arabic, stir well, pass nitrogen, expel the air, then add 1.4 g of tri(1-chloro-2-propyl) phosphate and 0.1 g of sodium carbonate. After the addition, turn on the heating until the temperature in the reactor reaches 70°C, keep stirring for 8 hours, discharge the material, place the material in a mold and let it stand. After gel is formed, transfer the mold to -20°C and store for 6 hours, then transfer it to a freeze dryer and freeze-dry it at -50°C for 36 hours to obtain a flame-retardant gas gel.

[0036] The modified gum arabic and flame retardant gel were analyzed by infrared spectroscopy using the i CAN9 Fourier transform infrared spectrometer produced by Tianjin Spectrum Technology Co., Ltd. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of modified gum arabic, 1759cm -1 The characteristic absorption peak of the ester group C=O appears at 3035cm -1 The characteristic absorption peak of CH in the benzene ring appears at 1606cm -1 The characteristic absorption peak of C=N appears at 3390cm -1 The characteristic absorption peak of NH appears at 1409cm -1 The characteristic absorption peak of CN appears at 1740cm -1 The characteristic absorption peak of the ester group C=O appears at 1601cm -1 The characteristic absorption peak of C=N appears at 1280cm-1 The characteristic absorption peak of P=O appears at 1065cm -1 The characteristic absorption peak of POC appears at 1415cm -1 The characteristic absorption peak of CN appears at the position, the absorption peak of CN is enhanced, and the absorption peak of NH disappears.

[0037] Technical principle: In the flame-retardant gas gel, firstly, the structure of gum arabic contains a large number of active hydroxyl groups, which can react with the carboxyl group in the structure of 1H-indazole-3-carboxylic acid under the action of tetrabutyl titanate, thereby introducing 1H-indazole-3-carboxylic acid into the structure of gum arabic to obtain modified gum arabic; secondly, under the action of sodium carbonate, the NH on the indazole ring in the modified gum arabic structure can undergo a substitution reaction with the phosphorus oxychloride group in the structure of tri(1-chloro-2-propyl) phosphate to obtain a flame-retardant gas gel.

[0038] 2. Preparation of Inorganic Modified Fillers

[0039] S1: 3 g of muscovite was added to a toluene solution, and ultrasonically dispersed for 20 min. Under continuous nitrogen conditions, 0.8 g of acrylic acid and 0.04 g of tetrabutyl titanate were added, and mechanical stirring was performed uniformly. The temperature was raised to 100° C. and kept warm for 5 h. The material was cooled naturally, and the solid material was separated by centrifugation. The solid material was washed and vacuum dried to obtain modified muscovite;

[0040] S2: Ultrasonic dispersion of 3 g of modified muscovite in dimethyl sulfoxide solution to form a dispersion, 2.5 g of polysulfide rubber and 0.08 g of benzoin ethyl ether were added to the dispersion, the system was placed under ultraviolet light for 3 h under stirring, the material was discharged, washed, and dried to obtain an inorganic modified filler.

[0041] The inorganic modified filler was analyzed by infrared spectrum using the iCAN9 Fourier transform infrared spectrometer produced by Tianjin Spectrum Technology Co., Ltd. Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of inorganic modified fillers, 1750cm -1 The characteristic absorption peak of the ester group C=O appears at 1035cm -1 The characteristic absorption peak of ether bond COC appears at 558 cm -1 The characteristic absorption peak of SS appears at 726cm -1 The characteristic absorption peak of CS appears at

[0042] Technical principle: In the inorganic modified filler, first, under the action of tetrabutyl titanate and high temperature, the hydroxyl groups on the surface of muscovite react with the carboxyl groups in the acrylic acid structure to undergo esterification reaction, thereby modifying the surface of the muscovite with unsaturated olefinic functional groups to obtain modified muscovite; secondly, under the irradiation conditions of benzoin ethyl ether and ultraviolet light, the unsaturated olefinic functional groups on the surface of the modified muscovite are used as active sites, and the mechanism that the unsaturated olefinic functional groups can undergo click reaction with the thiol groups in the polysulfide rubber structure is utilized to graft the polysulfide rubber to the surface of the muscovite to obtain the inorganic modified filler.

[0043] 3. Preparation of fireproof board

[0044] Step 1, add 50 parts of bamboo powder, 40 parts of polypropylene resin and 0.5 parts of titanate coupling agent PN-130 into a high-speed mixer, premix for 10 minutes, then add 3 parts of flame-retardant gas gel, 4 parts of inorganic modified filler, 1 part of calcium zinc stabilizer, 2 parts of dibutyl phthalate, 1 part of stearic acid and 1 part of antioxidant 1010, mix at high speed for 20 minutes to obtain a mixture;

[0045] Step 2: placing the mixture obtained in step 1 into a twin-screw extruder, setting the granulation temperature to 150° C. and the screw speed to 100 r / min, and performing melt extrusion granulation to obtain wood-plastic composite board pellets;

[0046] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 170° C. and a pressure of 8 MPa for 15 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0047] Example 2

[0048] Step 1, add 55 parts of bamboo powder, 45 parts of polypropylene resin and 0.7 parts of titanate coupling agent PN-130 into a high-speed mixer, premix for 15 minutes, then add 5 parts of flame-retardant gas gel, 6 parts of inorganic modified filler, 2 parts of calcium zinc stabilizer, 3 parts of dibutyl phthalate, 2 parts of stearic acid and 1.5 parts of antioxidant 1010, mix at high speed for 25 minutes to obtain a mixture;

[0049] Step 2: placing the mixture obtained in step 1 into a twin-screw extruder, setting the granulation temperature to 160° C. and the screw speed to 150 r / min, and performing melt extrusion granulation to obtain wood-plastic composite board pellets;

[0050] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 175° C. and a pressure of 9 Pa for 18 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0051] The preparation method of the flame retardant gas gel and the inorganic modified filler is the same as that in Example 1.

[0052] Example 3

[0053] Step 1, add 60 parts of bamboo powder, 50 parts of polypropylene resin and 0.9 parts of titanate coupling agent PN-130 into a high-speed mixer, premix for 20 minutes, then add 7 parts of flame-retardant gas gel, 8 parts of inorganic modified filler, 3 parts of calcium zinc stabilizer, 4 parts of dibutyl phthalate, 3 parts of stearic acid and 2 parts of antioxidant 1010, mix at high speed for 30 minutes to obtain a mixture;

[0054] Step 2: placing the mixture obtained in step 1 into a twin-screw extruder, setting the granulation temperature to 170° C. and the screw speed to 200 r / min, and performing melt extrusion granulation to obtain wood-plastic composite board pellets;

[0055] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 180° C. and a pressure of 10 MPa for 20 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0056] The preparation method of the flame retardant gas gel and the inorganic modified filler is the same as that in Example 1.

[0057] Comparative Example 1

[0058] Step 1, add 55 parts of bamboo powder, 45 parts of polypropylene resin and 0.7 parts of titanate coupling agent PN-130 into a high-speed mixer, premix for 15 minutes, then add 5 parts of flame-retardant gel, 2 parts of calcium zinc stabilizer, 3 parts of dibutyl phthalate, 2 parts of stearic acid and 1.5 parts of antioxidant 1010, mix at high speed for 25 minutes to obtain a mixture;

[0059] Step 2: placing the mixture obtained in step 1 into a twin-screw extruder, setting the granulation temperature to 160° C. and the screw speed to 150 r / min, and performing melt extrusion granulation to obtain wood-plastic composite board pellets;

[0060] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 175° C. and a pressure of 9 Pa for 18 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0061] The preparation method of the flame retardant gel is the same as that in Example 1.

[0062] Comparative Example 2

[0063] Step 1, add 55 parts of bamboo powder, 45 parts of polypropylene resin and 0.7 parts of titanate coupling agent PN-130 into a high-speed mixer, premix for 15 minutes, then add 6 parts of inorganic modified filler, 2 parts of calcium zinc stabilizer, 3 parts of dibutyl phthalate, 2 parts of stearic acid and 1.5 parts of antioxidant 1010, mix at high speed for 25 minutes to obtain a mixture;

[0064] Step 2: placing the mixture obtained in step 1 into a twin-screw extruder, setting the granulation temperature to 160° C. and the screw speed to 150 r / min, and performing melt extrusion granulation to obtain wood-plastic composite board pellets;

[0065] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 175° C. and a pressure of 9 Pa for 18 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0066] The preparation method of the inorganic modified filler is the same as that in Example 1.

[0067] Comparative Example 3

[0068] Step 1, add 55 parts of bamboo powder, 45 parts of polypropylene resin and 0.7 parts of titanate coupling agent PN-130 into a high-speed mixer, premix for 15 minutes, then add 5 parts of flame-retardant gas gel, 4 parts of muscovite, 2 parts of polysulfide rubber, 2 parts of calcium zinc stabilizer, 3 parts of dibutyl phthalate, 2 parts of stearic acid and 1.5 parts of antioxidant 1010, mix at high speed for 25 minutes to obtain a mixture;

[0069] Step 2: placing the mixture obtained in step 1 into a twin-screw extruder, setting the granulation temperature to 160° C. and the screw speed to 150 r / min, and performing melt extrusion granulation to obtain wood-plastic composite board pellets;

[0070] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 175° C. and a pressure of 9 Pa for 18 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0071] The preparation method of the flame retardant gel is the same as that in Example 1.

[0072] Comparative Example 4

[0073] Step 1, add 55 parts of bamboo powder, 45 parts of polypropylene resin and 0.7 parts of titanate coupling agent PN-130 into a high-speed mixer, premix for 15 minutes, then add 2 parts of calcium zinc stabilizer, 3 parts of dibutyl phthalate, 2 parts of stearic acid and 1.5 parts of antioxidant 1010, mix at high speed for 25 minutes to obtain a mixture;

[0074] Step 2: placing the mixture obtained in step 1 into a twin-screw extruder, setting the granulation temperature to 160° C. and the screw speed to 150 r / min, and performing melt extrusion granulation to obtain wood-plastic composite board pellets;

[0075] Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 175° C. and a pressure of 9 Pa for 18 minutes, and then cool and shape them in a cold press to obtain a fireproof board.

[0076] Performance testing:

[0077] The fireproof boards prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were made into samples that met the specifications, and the flame retardant properties of the samples were tested according to GB / T2406.1-2008 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 1: Guidelines"; the normalized impact sound pressure level of the samples was tested according to GB / T 19889.6-2005 "Acoustic Buildings and Building Components Sound Insulation Measurement Part 6: Laboratory Measurement of Floor Impact Sound Insulation" and GB / T 50121-2005 "Building Sound Insulation Evaluation Standard", and the sound insulation effect of the samples was evaluated. The specific test results are shown in Table 1:

[0078] Table 1 - Performance Test

[0079] Limiting oxygen index (%) Normalized impact sound pressure level (dB) Example 1 30.3 48 Example 2 30.8 47 Example 3 30.1 50 Comparative Example 1 28.2 59 Comparative Example 2 25.4 56 Comparative Example 3 28.6 54 Comparative Example 4 20.3 73

[0080] From the test results in Table 1, it can be seen that the fireproof boards prepared in Examples 1 to 3 all have excellent flame retardant and sound insulation properties; in the fireproof board prepared in Comparative Example 1, only flame retardant gas gel is added, and the flame retardant performance of the fireproof board is good, and its normalized impact sound pressure level is 59dB. Compared with the examples, the sound insulation performance of the fireproof board is average; in the fireproof board prepared in Comparative Example 2, only inorganic modified filler is added. Compared with the examples, the limiting oxygen index value of the sample decreases significantly, and it cannot cooperate with the flame retardant gas gel to produce a sound insulation effect, so The sound insulation performance of this fireproof board is average, and the flame retardant performance is poor; the fireproof board prepared in comparative example 3 is added with flame retardant gas gel, muscovite and polysulfide rubber. Compared with the embodiments, the flame retardant and sound insulation performance of the fireproof board are average. It is speculated that this may be because the unmodified muscovite is aggregated with each other in the matrix, resulting in agglomeration, which leads to a decrease in the flame retardant and sound insulation performance of the fireproof board; the fireproof board prepared in comparative example 4 has neither flame retardant gas gel nor inorganic modified filler added, so the performance of the fireproof board is the worst.

[0081] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A sound insulation and fireproof board, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of bamboo powder, 40-50 parts of polypropylene resin, 0.5-0.9 parts of titanate coupling agent PN-130, 3-7 parts of flame-retardant gas gel, 4-8 parts of inorganic modified filler, 1-3 parts of calcium zinc stabilizer, 2-4 parts of dibutyl phthalate, 1-3 parts of stearic acid and 1-2 parts of antioxidant 1010.

2. A sound insulation and fireproof board according to claim 1, characterized in that: The preparation method of the flame-retardant gas gel comprises the following steps: S1: Add gum arabic to a mixed solution of N,N-dimethylformamide and deionized water, stir evenly with a magnetic stirrer, pass nitrogen protection, then add 1H-indazole-3-carboxylic acid and a catalyst to the system, after the addition, turn on the heating, wait until the system temperature reaches 95-105°C, stir at a constant temperature for 4-6 hours, stop heating and remove nitrogen, cool to room temperature and then discharge to obtain modified gum arabic; S2: Add deionized water and toluene to the reactor, mix well, add modified gum arabic, stir well, pass nitrogen, expel air, then add tri(1-chloro-2-propyl) phosphate and alkaline catalyst, after the addition is completed, turn on the heating until the temperature in the reactor reaches 65-75°C, keep warm and stir for 6-10 hours, discharge the material, and freeze-dry to obtain a flame-retardant gas gel.

3. A sound insulation and fireproof board according to claim 2, characterized in that: In step S1, the catalyst is any one of tetrabutyl titanate, tetraethyl titanate or tetraisopropyl titanate.

4. A sound insulation and fireproof board according to claim 2, characterized in that: In step S2, the alkaline catalyst is any one of sodium carbonate, potassium carbonate or sodium bicarbonate.

5. The sound insulation and fireproofing board according to claim 2, characterized in that: In step S2, the freeze-drying process is as follows: placing the material in a mold and letting it stand, after forming a gel, transferring the mold to a temperature of -15 to -25°C and storing it for 5 to 8 hours, and then transferring it to a freeze dryer and freeze-drying it at -48 to -52°C for 24 to 48 hours.

6. The sound insulation and fireproofing board according to claim 1, characterized in that: The preparation method of the inorganic modified filler comprises the following steps: SS1: Add muscovite to toluene solution, ultrasonically disperse for 15-25 minutes, add acrylic acid and tetrabutyl titanate under continuous nitrogen conditions, mechanically stir evenly, raise the temperature to 95-105°C, keep warm for 3-6 hours, wait for the material to cool naturally, centrifuge to separate the solid material, wash the solid material, and vacuum dry to obtain modified muscovite; SS2: Ultrasonic dispersion of modified muscovite in dimethyl sulfoxide solution to form a dispersion, polysulfide rubber and photoinitiator are added to the dispersion, the system is placed under ultraviolet light for 1 to 4 hours under stirring, the material is discharged, washed, and dried to obtain an inorganic modified filler.

7. A sound insulation and fireproof board according to claim 6, characterized in that: In step SS2, the mass ratio of the modified muscovite to the polysulfide rubber is 1:0.4-0.

9.

8. The sound insulation and fireproofing board according to claim 6, characterized in that: In step SS2, the photoinitiator is any one of benzoin ethyl ether, benzoin isopropyl ether or benzoin dimethyl ether.

9. The sound insulation and fireproofing board according to claim 1, characterized in that: The preparation method of the fireproof board comprises the following steps: Step 1, adding bamboo powder, polypropylene resin and titanate coupling agent PN-130 into a high-speed mixer, premixing for 10 to 20 minutes, then adding inorganic modified filler, flame retardant gel, calcium zinc stabilizer, dibutyl phthalate, stearic acid and antioxidant 1010, and mixing at high speed for 20 to 30 minutes to obtain a mixture; Step 2: placing the mixed material obtained in step 1 in a twin-screw extruder, setting the granulation temperature to 150-170° C., the screw speed to 100-200 r / min, and melt-extruding and granulating to obtain wood-plastic composite board pellets; Step 3: Place the wood-plastic composite board pellets obtained in step 2 in a hot press, perform hot pressing treatment at a temperature of 170-180°C and a pressure of 8-10 MPa for 15-20 minutes, and then cool and shape them in a cold press to obtain a fireproof board.